MAPA HIDROGEOLÓGICO DA AMÉRICA DO SUL, ESCALA 1:5.000.000 - METODOLOGIA DE TRABALHO - Mente, Albert; Mont’Alverne, Alarico Antônio Frota; V., Eugenio Godoy (Águas Subterrâneas, 1988)
Resumo não disponível.